Trade costs shocks and lumpiness of imports: Evidence from the Fukushima disaster - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
This paper uses a difference-in-differences approach to test the hypothesis that the increase in the per-shipment costs of imports from Japan due to the Fukushima disaster in 2011 lead to an increase in the lumpiness of imports from Japan. Using China and the USA as control groups it is found that the Fukushima trade cost shock reduced the average number of import transactions per year at the firm-good level and, therefore, increased the degree of lumpiness of imports from Japan.
Keywords: F14; 330; Fukushima disaster; trade shock; imports; Germany